Anticholinergic Drugs and Oral Health-related Quality of Life in Patients with Schizophrenia: A Pilot Study - Chapuis, Justine (Transl Neurosci, 2020)
OBJECTIVE: The aim of this study was to explore, in a sample population of people with schizophrenia (PWS), the role of the anticholinergic burden on the perception of oral health-related quality of life (OHrQoL) in France. METHODS: A pilot study was performed between March 2014 and January 2016. PWS were recruited from a population in Côte d’Or department in France. Dental status was investigated using the Decayed, Missing, or Filled Teeth (DMFT) index, the Xerostomia Index (XI), and the Global Oral Health Assessment Index (GOHAI) for OHrQoL. The anticholinergic impregnation score was recorded using the anticholinergic impregnation scale (AIS). RESULTS: A sample of 62 people was selected. The DMFT score was 16.5± 8.7, the XI score was 22.9±7.8, the GOHAI score was 43.0±8.8, and the AIS score was 3.1±2.8. In total, 169 drugs were prescribed to the people of our sample, and 114 different anticholinergic drugs were observed. The most frequently used anticholinergic drugs (51.40%), in the study had a low antimuscarinic potency (1 point according to AIS scale). The multiple linear regression model showed that the OHrQoL scores were significantly lower when the DMFT scores, XI score, and anticholinergic scores were high. CONCLUSIONS: This pilot study highlighted the potential role of the anticholinergic burden on the OHrQoL of PWS. A study with a validated specific scale for the OHrQoL and a standard anticholinergic burden scale should be conducted to clarify the role of anticholinergic drugs on the OHrQoL for PWS.